Regulation of cell-type-specific transcriptomes by microRNA networks during human brain development. (December 2018) - Nowakowski, Tomasz; Rani, Neha; Golkaram, Mahdi; Zhou, Hongjun; Alvarado, Beatriz; Huch, Kylie; West, Jay; Leyrat, Anne; Pollen, Alex; Kriegstein, Arnold; Petzold, Linda; Kosik, Kenneth
Abstract MicroRNAs (miRNAs) regulate many cellular events during brain development by interacting with hundreds of mRNA transcripts. However, miRNAs operate nonuniformly upon the transcriptional profile with an as yet unknown logic. Shortcomings in defining miRNA–mRNA networks include limited knowledge of in vivo miRNA targets and their abundance in single cells. By combining multiple complementary approaches, high-throughput sequencing of RNA isolated by cross-linking immunoprecipitation with an antibody to AGO2 (AGO2-HITS-CLIP), single-cell profiling and computational analyses using bipartite and coexpression networks, we show that miRNA-mRNA interactions operate as functional modules that often correspond to cell-type identities and undergo dynamic transitions during brain development. These networks are highly dynamic during development and over the course of evolution. One such interaction is between radial-glia-enriched ORC4 and miR-2115, a great-ape-specific miRNA, which appears to control radial glia proliferation rates during human brain development. Highly dynamic miRNA networks mediate developmental transitions during human brain development. Single-cell networks were detected by combining single-cell miRNA and mRNA profiling with HITS-CLIP analyzed with bipartite and co-expression networks.